Developmental Abnormalities Associated with a Ring Chromosome 6 - Moore, C. M. (1973)
A clinical and cytogenetic report is made of a patient with microcephaly, peculiar facies, and retardation of physical and mental development, who possesses a karyotype containing a ring chromosome No. 6 identified by Q-staining with quinacrine mustard. This is the first report of a ring autosome in the C group to be identified. Comparison with other patients reported as having C-group autosomal rings failed to reveal many common phenotypic characteristics.